Workshop on research priorities in tidal swamp rice (International Rice Research Institute, 1984)
The book selects the papers presented on the workshop held at Banjarmasin, Kalimantin Selatin, Indonesia. The workshop identified new technologies that, by a concerted research effort, could be generated for the fragile environment of tidal swamps identified the problems unique to the tidal swamp areas